GUI Inspection from Source Code Analysis - Silva, Joao; Creissac, José; Saraiva, Joao (Electronic Communications of the EASST, 2010)
Graphical user interfaces (GUIs) are critical components of todays software. Given their increased relevance, correctness and usability of GUIs are becoming essential. This paper describes the latest results in the development of our tool to reverse engineer the GUI layer of interactive computing systems. We use static analysis techniques to generate models of the user interface behaviour from source code. Models help in graphical user interface inspection by allowing designers to concentrate on its more important aspects. One particular type of model that the tool is able to generate is state machines. The paper shows how graph theory can be useful when applied to these models. A number of metrics and algorithms are used in the analysis of aspects of the user interface’s quality. The ultimate goal of the tool is to enable analysis of interactive system through GUIs source code inspection.